Pemberdayaan Kelompok Rentan di Desa Oenoni Kecamatan Amarasi Nusa Tenggara Timur dengan Mengimplementasikan Rancangan Rumah K-Poinoni - Crystia Aji Putra; Dedin Finatsiyatul Rosida; Mei Rahayuningtyas Widodo; Abid Bahij Alhisyam (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
The efforts of the Kupang Region 3T KKN Students consisting of UPN "Veteran" East Java students and the University of Jember in empowering vulnerable groups in Oenoni Village were carried out with the establishment of the K-Poinoni House which is a big step towards the progress of the humanist Oenoni village through the development of inclusive and sustainable entrepreneurship. This K-Poinoni House is expected to create an inclusive, productive, and sustainable environment, which is able to bring Oenoni Village towards progress and shared prosperity. Overall, Rumah K-Poinoni is expected to bring significant positive change, create welfare, and support sustainable development in the village.